A New Species of the Boana albopunctata Group (Anura: Hylidae) from the Cerrado of Brazil - Pinheiro, Paulo D. P. [UNESP]; Cintra, Carlos E. D.; Valdujo, Paula H.; Silva, Helder L. R.; Martins, Itamar A.; Silva, Nelson Jorge da; Garcia, Paulo C. A. (Soc Brasileira Herpetologia, 2018)
We describe a new species of Boana endemic to the Araguaia-Tocantins Basin in the center of the Brazilian Cerrado that was previously confused with species of the B. pulchella group. The new species is tentatively included in the B. albopunctata group on the basis of morphological and bioacoustics traits. The new species is characterized by a rounded head in dorsal view, dorsal color pattern consisting of three longitudinal beige stripes separated by two dark-brown stripes, posterior surfaces of thighs purple with dark-brown spots, and absence of a calcar appendage. Males have a pulsed advertisement call, with the end of the first note possessing an uncountable number of pulses. The new species differs from species of the B. pulchella group by the presence of a slip of the m. depressor mandibulae of scapular origin, presence of anterolateral processes of the hyoid, and curved dentigerous processes of vomers.
Keywords: Amphibia; Bioacoustics; Neotropics; Systematics; Taxonomy